2017
DOI: 10.4047/jap.2017.9.2.93
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the width ratio and wear rate of maxillary anterior teeth in the Korean population

Abstract: PURPOSEThe purpose of this study was to compare the width ratio of maxillary anterior teeth according to age in the Korean population and to evaluate the maxillary central incisor width-to-length (W/L) ratio, given differences in age and gender.MATERIALS AND METHODSNinety-three Korean adults were divided into 3 groups (n = 31) by age. Group I was 20 - 39 years old, Group II was 40 - 59 years old, and Group III was over 60 years of age. After taking an impression and a cast model of the maxillary arch, the ante… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In the second phase of study selection, full‐text analysis was performed for 77 articles, resulting in 23 meeting the inclusion criteria and was, therefore, included in this systematic review (Figure 2). This review of the literature is based on 23 articles published from March 20, 2010, to July 25, 2019 2,8,9,17,18,20,21,25‐34 . In all, data from 3603 participants were recorded.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the second phase of study selection, full‐text analysis was performed for 77 articles, resulting in 23 meeting the inclusion criteria and was, therefore, included in this systematic review (Figure 2). This review of the literature is based on 23 articles published from March 20, 2010, to July 25, 2019 2,8,9,17,18,20,21,25‐34 . In all, data from 3603 participants were recorded.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the different classifications included were the groups comparable, were cases and controls matched appropriately, were the same criteria used for identification of cases and controls, was exposure measured in a standard, valid, and reliable way, was exposure measured in the same way for cases and controls, and were confounding factors identified (Table 1, Figure 3). 8,9,17,18,20,21,[25][26][27][28][29][30][31][32][33][34] In all, data from 3603 participants were recorded. Data collected was reported from each study.…”
Section: Quality Assessmentmentioning
confidence: 99%
“…Clinically, it is often found that there is obviously transparent enamel in the central incisors of young people. Furthermore, the translucency in the senior group was higher than that in the middle-aged group, which might be related to the reduction in the incisal edge thickness of the central incisors 26) . At the same time, the dentin also displayed an increasing trend of translucency with age 3) , which also led to the increase in translucency in the central incisors.…”
Section: Discussionmentioning
confidence: 84%
“…Analysis of the golden ratio in different ethnicities show that countries such as Saudi Arabia, India, Japan, Turkey and Ireland present in their population some references to the measurements established by the golden ratio [14][15][16][17][18][19][20], whilst Korea, Pakistan, Colombia, China, Hungary, Malaysia, Iran and Brazil [21][22][23][24][25][26][27][28][29][30][31][32] did not show any relation to the golden ratio.…”
Section: Ethnic Groupsmentioning
confidence: 99%